Dwindling Resources and Funding: Superintendents’ Leadership and School Board Members’ Decision-Making and Students’ Well-being and Academic Outcomes Remain a Challenge - Hilliard, Ann Toler; Foose, Renee A.; Kargbo, Harriett; Jackson, Charles H. Talbert (Advances in Social Sciences Research Journal, 2022)
Superintendents have many challenges in performing the job in most school districts. A high percentage of superintendents see the most challenging tasks are to improve the performance of diverse underprepared students, how to help students who come to school from high poverty areas who need so much help and recruiting and maintaining quality teachers to work in schools. Other challenges for superintendents are strengthening academic rigor, budget shortfalls, recruiting and retaining principals/teachers, and rising demands for assessment from the state and federal levels. Superintendents are concerned about students being safe in schools, being successful in careers and education in post- secondary settings in a rapidly changing economy and a highly technologically driven society (Noonoo, 2018).